2018
DOI: 10.4314/sajas.v48i1.19
|View full text |Cite
|
Sign up to set email alerts
|

Feed preference of grower ostriches consuming diets differing in <i>Lupinus angustifolius</i> inclusion levels

Abstract: Feed costs contribute the largest proportion of the input costs of slaughter birds in an intensive ostrich production unit. Alternative, cheaper feedstuffs, such as lupins (sweet and bitter cultivars), were therefore evaluated to determine the optimal lupin inclusion level in ostrich rations without affecting feed preference and intake. Sixty South African Black ostriches were randomly divided into ten paddocks of six birds per paddock. Three trials, with five different experimental diets, were conducted to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…According to Hughes et al [40], whole seeds of lupins can be included up to 200 and 300 g/kg in wheat-based and maize-based diets, respectively, for broilers. Brand et al [52] reported that SBM can be replaced with sweet lupins up to 300 g/kg in the diet of grower ostriches. It is, however, worth noting that higher inclusion levels of lupins could increase the incidence of wet litter [38,40].…”
Section: Feeding Trialsmentioning
confidence: 99%
“…According to Hughes et al [40], whole seeds of lupins can be included up to 200 and 300 g/kg in wheat-based and maize-based diets, respectively, for broilers. Brand et al [52] reported that SBM can be replaced with sweet lupins up to 300 g/kg in the diet of grower ostriches. It is, however, worth noting that higher inclusion levels of lupins could increase the incidence of wet litter [38,40].…”
Section: Feeding Trialsmentioning
confidence: 99%
“…This Lesnov's ferment preparation is a combination of elk ruminal fluid and specific plants extract with high biological activity (Lesnov, 1998;Lesnov & Lesnova 2002;Lesnov&Lesnova 2003;Popova 2009). It has been well reported that that broilers fed on fermented diets have higher BW and improved feed conversion as compared to the traditional broilers feed (Brand et al, 2018).…”
Section: Introductionmentioning
confidence: 99%